السياسات والتجارب الدولية الرائدة في مجال التنويع الاقتصادي حالة (ماليزيا واندونيسيا والمكسيك) - غلاب فاتح غلاب فاتح; سعيداني محمد السعيد سعيداني محمد السعيد; رزيقات بوبكر رزيقات بوبكر (Finance and Business Economies Review, 2017)
<span dir="ltr" style="left: calc(var(–scale-factor)*68.42px); top: calc(var(–scale-factor)*520.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935168);" role="presentation">The global economic environment has undergone major changes as a result of the sharp decline and <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*539.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.977369);" role="presentation">possibly chronic in oil prices, and the consequent weakening of <span dir="ltr" style="left: calc(var(–scale-factor)*328.27px); top: calc(var(–scale-factor)*539.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87931);" role="presentation">Balances <span dir="ltr" style="left: calc(var(–scale-factor)*373.51px); top: calc(var(–scale-factor)*539.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.979068);" role="presentation">foreign and finance public <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*556.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934606);" role="presentation">accounts and weaken governance and institut<span dir="ltr" style="left: calc(var(–scale-factor)*242.93px); top: calc(var(–scale-factor)*556.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.961535);" role="presentation">ions in the countries, and experts say the achievement of <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*574.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908811);" role="presentation">tangible progress in reducing dependence on oil as a major source of export revenues and public finance, It <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*591.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940625);" role="presentation">requires governments to adopt an economic model. And historical experiences tell us a few <span dir="ltr" style="left: calc(var(–scale-factor)*435.34px); top: calc(var(–scale-factor)*591.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921453);" role="presentation">examples of <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*608.71px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951551);" role="presentation">countries and possibly Malaysia, Indonesia and Mexico are the best models for countries succeeded in <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*625.99px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.985285);" role="presentation">diversifying their economies away from a focus on the oil. Although follow each of these countries a <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*643.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.923063);" role="presentation">different path, it is clear that among the<span dir="ltr" style="left: calc(var(–scale-factor)*212.93px); top: calc(var(–scale-factor)*643.27px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918294);" role="presentation">m some of the things common among them: providing incentives to <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*660.46px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922096);" role="presentation">encourage companies to develop export markets and to support employment in the skills and education of <span dir="ltr" style="left: calc(var(–scale-factor)*53.88px); top: calc(var(–scale-factor)*677.74px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931601);" role="presentation">appropriate addition to finding a stable economic environment and a climate conducive <span dir="ltr" style="left: calc(var(–scale-factor)*413.14px); top: calc(var(–scale-factor)*677.74px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*423.46px); top: calc(var(–scale-factor)*677.74px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.932243);" role="presentation">doing <span dir="ltr" style="left: calc(var(–scale-factor)*448.66px); top: calc(var(–scale-factor)*677.74px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.857535);" role="presentation">business.